THE IMPACT OF DIFFERENT CHARACTERISTICS AND MODALITIES OF PHYSICAL ACTIVITY ON HEALTH VARIABLES IN ELDERLY PEOPLE WITH TYPE 2 DIABETES - Rodionova, Karina; Kļaviņa, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Type 2 diabetes (T2D) comprises 90% of people with diabetes around the world, and is largely the result of excess body weight and physical inactivity (WHO, 2015). Objective: To evaluate and analyze evidence based research studies exploring the impact of physical activity on health variables in elderly population age 50-70 years with T2D.Data sources: Web of Science, CINAHL, SCOPUS, EMBASE, MEDLINE, PubMed and SPORTdiscus data bases were used for screening and selecting relevant research studies over the period 2005-2015.Study Selections: Randomized controlled trials (RCTs). Population: older adults or elderly with T2D. Intervention: All types of physical activity such as interval walking, aquatics or free living activity were included. Outcomes: glycemic control, lipid profile, insulin sensitivity, BMI, blood pressure and VO₂max. Methodological quality was assessed using the Delphi List.Data Synthesis: While 1773 potentially relevant studies were found and 213 RCTs were relevant to the topic, only 16 studies (patients n= 946) accepted to the review. Results: The circuit resistance training was associated with hemoglobin A1c (HbA1c) decrease (8.0 (.35) to 7.36 (.28)), body mass index (BMI) reduction from 22.0(.8) to 20.9 (.8) and body weight change from 53.3 (1.6) to 51.9 (1.7). Improvement of insulin sensitivity, VO2max and glycemic control were observable in 8 studies including 16-week aerobic exercise training, 16-week interval walking training, and combined aerobic and resistance training. Combination of aerobic and resistance exercises were associated with positive change in plasma fasting glucose and were 6.86 (1.40) and 6.19 (1.47).Conclusions: The most effective and time consuming physical activity is interval walking, circuit training or combination of different intensity and/or physical activity modalities.